Colonic (splenic flexure) necrosis due to thrombosis of the middle colic artery following blunt abdominal trauma - Coimbra, Raul; Aguiar, José Ribeiro; Rasslan, Samir; Ressurreição, Silvio Pires (São Paulo Medical Journal, 1994)
We report an unusual case of a 28-year-old man who developed a colonic necrosis due to thrombosis of the middle colic artery 18 hours following blunt abdominal trauma. Although rare, this condition can occur in those patients whom non surgical treatment was initially performed.